2010
DOI: 10.1029/2009ja014903
|View full text |Cite
|
Sign up to set email alerts
|

Experiment based on spacesuit “Orlan‐M”: Neutron fluxes from thunderstorms

Abstract: [1] We present a new experiment on the detection of thunderstorm neutrons at orbital altitudes. The aims of the experiment called "Scafandr" are to establish the nature of the neutrons and to explore their properties. Also, the dosimetric measurement program is included in the experiment mission. For the neutron program, measurement of the thermal neutron fluxes from an altitude of 350 km down to 200 km is planned. We plan to obtain substantial statistics and resolution of neutron bursts. This will allow for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The other result in TAE study could be connected to the possibilities of neutron detection. Simulation predicts detection of about two neutrons for event time 30 ms at the orbit with 450 km altitude, by the detector with 60 cm 2 effective area (Drozdov et al (2010); Grigoriev et al (2010)). This result implies that detection of significant number of neutrons from TGFs is possible using the detector with effective area of about several hundred square centimeter.…”
Section: Discussion and Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The other result in TAE study could be connected to the possibilities of neutron detection. Simulation predicts detection of about two neutrons for event time 30 ms at the orbit with 450 km altitude, by the detector with 60 cm 2 effective area (Drozdov et al (2010); Grigoriev et al (2010)). This result implies that detection of significant number of neutrons from TGFs is possible using the detector with effective area of about several hundred square centimeter.…”
Section: Discussion and Resultsmentioning
confidence: 96%
“…The simulation of neutrons generated by gamma quanta during their propagation in the atmosphere was made also by (Drozdov et al 2010) and (Grigoriev et al 2010). They simulated the albedo neutron background and thunderstorm-produced neutrons, and then compared albedo and thunderstorm neutrons spectral parameters to estimate possibility of thunderstorm neutron detection in orbits with different altitudes up to 450 km.…”
Section: The Specific Problems Of Tgf Studymentioning
confidence: 99%
“…Completing our brief report we would like to pay attention to some observations that can be done on the basis of the obtained results. In the work of Drozdov et al [2010] a peculiarity is indicated consisting in the lack of the neutron bursts over the American near‐equatorial thunderstorm system while over the other main near‐equatorial thunderstorm systems (Asian, Pacific and African) they were detected. It is a kind of small obstacle for the nowadays conventional view on the origin of the neutrons.…”
Section: Discussionmentioning
confidence: 99%
“…For the needs of the experiment “Radioskaf,” we elaborated the CA scheme modeling neutrons transport in matter. The experiment is planned to conduct at the Moscow Sate University [ Drozdov et al , 2010]. The goals of the experiment are to prove the idea of neutron generation in thunderstorms, to explore main neutron fluxes features and to throw the light on the neutrons nature.…”
Section: Analysis and Modelingmentioning
confidence: 99%
See 1 more Smart Citation